Edifícios de escritório sustentáveis: O que muda na percepção de trabalhadores em home office - Leonardo Alcará Castelo (2021)
The search for a sustainable built environment has directed studies to different stages of the life cycle of a building. It is widely agreed that in buildings, the stage of use and occupation is the one that most generates environmental impact, thus being an important area of study. In this perspective, and in the context of the investigation of energy performance, the literature shows that the behavioral variables of users within the built environment can influence their energy consumption, which may be twice as much as predicted. At the beginning of data collection for this research, Brazil and the world were affected by the public health crisis as a result of the Covid-19 pandemic. Through this scenario, people's routines were changed, causing many of the activities that were previously external, to be developed within the built environments. In this sense, recent studies indicate that the changes caused by the pandemic go beyond the change in physical space, but also affect behavior and environmental awareness. In view of this, the following question arises: What are the factors of the energy consumption habit related to the work carried out in the home office that could contribute to the sustainable practices of energy consumption in office buildings? Therefore, the general objective of this research is to investigate the energy consumption habits related to working in the home office, during the pandemic period, and their possible contributions to sustainable practices in office buildings. In order to achieve this objective, the following specific objectives were accomplished: a) to elaborate a questionnaire that allows to measure the behavioral factors of energy consumption practices; b) to assess the occurrence of behavioral factors of energy consumption in home office workers, and finally, c) to analyze the influence of these behavioral factors in the habit of energy consumption in the work environment. As a result, the present study prepared a questionnaire in the light of the Theory of Planned Behavior that allowed obtaining important feedbacks for energy management regarding sustainable practices in office environments.